Challenges in Implementing the Thematic Calendar in Anganwadis of Kerala: Perspectives of Anganwadi Workers - K.P., Kadeeja Sanam; K., Abdul Gafoor (Voices of Teachers and Teacher Educators, 2021)
In the context of the thematic calendar, a curriculum for early years has been introduced by Integrated Child Development Services with the objective of holistic development of the children of 3-6 years. This study explores the challenges faced by the Aanganwadi workers in implementing the thematic calendar. Semi-structured interviews were conducted with thirty 30 Aanganwadi workers who were selected randomly from Kozhikode urban and rural projects of ICDS in Kerala. Thematic analysis was used to analysze the interview responses. It was found that challenges in implementing the curriculum in Aanganwadis relates to enrolment, learning aids, teaching-learning practices, infrastructure and logistic facilities, other services, financial assistance, supervision and training and honorarium. Measures to overcome the challenges and improve the practices of Aanganwadi workers are suggested.